Analysis of active pharmaceutical ingredients in 20 species of traditional Malay midwifery postnatal bath - Othman, Rashidi; Abdul Halim, Siti Farah Aliyah; Jamaluddin, Mohd Jamil Aizat (2015)
Midwifery is the practice of assisting a woman through childbirth using natural procedures.In Malay midwifery practices, traditional bath is one of the most important treatments during the confinement periods. However, today in Malay community, midwifery traditional knowledge of herbal medicine is disappearing and extinct. The facts are Malay midwives are becoming rare and the more crucial is medicinal plants are over-harvested. Therefore the aim of the research is to investigate the active pharmaceutical ingredients content in 20 selected species used in Malay midwifery practices during traditional bath. Thus, there is a solid need to analyse the potential of these natural bioactive compounds particularly carotenoids to be fully utilised and commersialised especially in halal market and health advantages. Through HPLC analysis all 20 species were found to have at least four individual carotenoid pigments with a relatively high concentration of lutein and β-carotene and lower concentrations of zeaxanthin. Surprisingly in every of 20 malay midwifery species samples used in traditional postnatal bath a relatively high lutein and β-carotene were detected. Selection of the right species with the right composition to accumulate lutein and β-carotene still remain mystery and mystic. The significant outcome of the research will be new findings of new natural bioactive compound sources as health promoting agents which covers not only the Shariah requirement, but also safety aspects.